Determination of Myocardial FFA Elimination Rates by Functional Images of Uncorrected Half-Time Values - Visser, F. C.; Van Lingen, A.; Westera, G.; van, M. J. Eenige; Den Hollander, W.; Van der Wall, E. E.; Heidendal, G. A. K.; Roos, J. P. (Nuklearmedizin - NuclearMedicine, 1984)
This paper presents an alternative method of demarcating regions of in terest over the myocardium after ad ministration of 123I-heptadecanoic acid to patients with coronary artery disea se. In a matrix of 32 × 32 pixels the elimination rates of the radioactivity, which are not corrected for back ground activity, are visualized per pixel in a functional image. The func tional image showed areas in the myocardium with high values of uncorrected elimination rates. These areas corresponded with the tracer defects on the scintigram. Corrected elimination rates obtained from re gions of interest of functional images were comparable with those of scinti grams. Thus based on functional im ages of uncorrected elimination rates a reliable, objective determination of regions of interest over normal and abnormal myocardium can be made.